Factors influencing classroom participation: a case study of Malaysian undergraduate students - Mustapha, Siti Maziha; Nik Abdul Rahman , Nik Suryani; Mohd Yunus, Melor (Elsevier, 2010)
Despite the importance often assigned to participation in classroom, it has been repeatedly reported that most students remain passive in class. This study aims to document influencing factors that shape undergraduate students’ participation in Malaysian classrooms. Interviews and observations were carried out. 85 students from two communication classes were observed over the period of two semesters (28 weeks). Most of the participants fell between the age of 18-19 years old (65.8%) and 66.7% of the participants were female while 33.3% were male. 25 students from the two classes were interviewed. The results strongly endorse that lecturer traits and classmate traits play significant roles in promoting student participation. Recommendations are offered to educators in formulating future teaching strategies that promote students’ participation in the context of higher learning